Pengujian Aktivitas Social Media Marketing terhadap Continuance Intention: Peran Kepuasan Pelanggan - Zahram, Zacky Zulfikar; Tjahyadi, Rully Arlan (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2023)
The proliferation of social media has reflected society's need for virtual interaction. Currently, social media plays a crucial role not only for seeking information and communication but also as a significant marketing platform. This phenomenon indicates that companies are capable of utilizing social media as an integral part of their online marketing strategy. This research aims to determine the influence of social media marketing on customer satisfaction and continuance intention. Explanatory research method were used to explain the influence between the dependent and independent variables in the hypothesis. Each proposed hypothesis in this study was tested using descriptive statistical analysis, path analysis, and hypothesis testing through the SPSS statistical analysis. The sample consists of individuals who use TikTok social media application. The sampling method used is purposive sampling. Data for this research were collected using a questionnaire from 200 samples. The results indicate that social media marketing significantly influences customer satisfaction and continuance intention. The other result indicate that customer satisfaction as a partial mediation. The implication of this research result is the importance of utilizing social media marketing activities as a tool to enhance customer interaction, increase product information, brand exposure, as well as build communities, which ultimately can influence customer attitudes and behaviors.